Body condition score sapi Bali induk dan temperature-humidity index di Kecamatan Tidore Utara, Kota Tidore Kepulauan - Maman Jafar; Eny Endrawati; Dwi Nur Happy Hariyono (Fakultas Pertanian Universitas Majalengka, 2023)
This study aimed to determine the body condition score (BCS) of Bali cows kept on smallholder farms and the temperature-humidity index (THI) in the Tidore Utara sub-district, from June to July 2022. Eighteen cows (2-3 years old) were selected on the basis of their BCS through direct observation (scoring scale: 1-5). The BCS data were analyzed as percentages (%) for each scoring scale and presented in a chart. The THI value was determined based on temperature (ºC) and humidity (%) data and analyzed using descriptive statistics as mean and standard deviation. The results showed that the average temperature in the morning and evening at the study site was relatively the same (32.00±3.14ºC vs. 32.01±1.17ºC), while the average humidity in the two-time groups was relatively different (87.89±11.14% vs. 77.96±6.50%). The average THI in the morning and evening (88.71±3.23 vs. 85.67±1.00) indicated that the cows in the study site experienced severe heat stress. The majority of the cows had BCS 3 (46.67%), while the remaining cows had BCS 2 (33.33%), BCS 4 (13.33%), and BCS 1 (6.67%). None of the cows had BCS 5 (0%).